3C-SiC on Si: A Versatile Material for Electronic, Biomedical and Clean Energy Applications. Issue 1693 (10th June 2014) - Frewin, C.L; Reyes, M.; Register, J.; Thomas, S. W.; Saddow, S. E.
Abstract: Silicon carbide (SiC) has long been known as a robust semiconductor with superior properties to silicon for electronic applications. Consequently a tremendous amount of international activity has been on-going for over four decades to develop high-power solid state SiC electronics. While this activity has focused on the hexagonal polytypes of SiC, the only form that can be grown directly on Si substrates, 3C-SiC (or cubic SiC), has been researched for non-electronic applications such as MEMS and biosensors. In particular in our group we have pioneered several biomedical devices using 3C-SiC grown on Si substrates, and recently have been investigating the use of this novel material for clean energy applications. This paper first reviews progress made in the area of 3C-SiC electronic devices. Next a review of nearly a decade of biomedical activity is presented, with particular emphasis on the most promising applications: in vivo glucose monitoring, biomedical implants for connecting the human nervous system to advanced prosthetics, and MEMS/NEMS research aimed at allowing for in vivo diagnostic and therapeutic systems for advanced biomedical applications. Recent published work in the area of hydrogen production via electrolysis using 3C-SiC closes the paper as this last application is extremely promising for the burgeoning hydrogen economy and demonstrates a third important application of 3C-SiC on Si – its potential use in clean energy systems.